Reinventing Data Protection? - Gutwirth, Serge.; Poullet, Yves.; Hert, Paul.; Terwangne, Cčile.; Nouwt, Sjaak. (Springer Netherlands, 2009)
This book is about data protection, privacy and liberty and the way these fundamental values of our societies are protected and enforced, particularly in their interaction with the ever developing capacities and possibilities of information and communication technologies. The authors are all closely involved in data protection and privacy. They represent the stakeholders in the debate: practitioners, civil liberties advocates, civil servants, data protection commissioners and academics. Their contributions evaluate current European data protection law against the background of the introduction of increasingly powerful, miniaturized, ubiquitous and autonomic forms of computing. The book assesses data protection and privacy law by analyzing the actual problems (trans-border data flows, proportionality of the processing, and sensitive data) and identifying lacunae and bottlenecks, while at the same time looking at prospects for the future (web 2.0., RFID, profiling) and suggesting paths for a rethinking and reinvention of the fundamental principles and concepts. From this perspective the recent constitutional acknowledgment of data protection as a fundamental right has a transformative power and should create the opportunity for a dynamic, participative, inductive and democratic process of <U+0018>networked<U+0019> re-invention of data protection. The present book aims to make a contribution by seizing on this opportunity.